Canon law or ecclesiastical law? - GAŁKOWSKI , TOMASZ (Prawo Kanoniczne, 2019)
In the Polish science of canon law there is a tendency to distinguish canon law from Church law. The first one concerns the law included in the Code of canon law and the latter the other acts of established law. The author of the study analyses the historical meaning of the terms canon law and Church law as equivalent terms for describing the same experience of law in the Church community. However, he believes that in the current state of knowledge the phrasing Church law better expresses the relationship between law and the nature of Church than the traditional phrasing canon law.